Portrait of Arabic Language Activity Model for Students of Al-Amanah Modern Islamic Boarding School, Sidoarjo, Indonesia - Rochmawati, Nur; Taufiq, Mirwan Akhmad; Romdlon, Atiq Mohammad; Rady, Mohammed jassim Mohammed (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2025)
This study aims to identify models of activities that can enhance Arabic language skills at the Al-Amanah Islamic Boarding School. The objective is to explore the types of language activities that strengthen students' Arabic skills and the assessment forms applied at the school. The methodology used is descriptive qualitative, with data collected through in-depth interviews with teachers, language department management, and students proficient in Arabic, along with documentation of the learning materials used. The results show that Arabic language activities at the school include four activities: vocabulary enhancement, speaking skills in daily life, lectures, and an intensive Arabic program for new students. These activities significantly improve students' ability to speak Arabic, focusing on education that supports speaking practice through memorisation, reading vocabulary, and speaking in Arabic.